Cancer Incidence in Samoa: A 10-Year Retrospective Survey (2007-2016). (September 2021) - Amosa-Lei Sam, Filipina; Akinremi, Ayodele; Mery, Les; Sarfati, Diana; Stanley, James; Gurney, Jason
Samoa is not immune to the growing global incidence of cancer, which is disproportionately high in low- and middle-income countries. As a preliminary step to upscale our population-based cancer registry initiatives in Samoa, we conducted a 10-year survey of cancer incidences in Samoa from 2007 to 2016. We reviewed all laboratory and clinically confirmed cases of cancer from 2007 to 2016 covering both government and nongovernment facilities. Cancer incidence increased steadily from 2007 (28.5 per 100 000) to 2012 (67.1 per 100 000). The incidence rate decreased in 2013 (from 67.1 cases in 2012 to 51.4 cases per 100 000 in 2013); and in 2015 (from 65.1 cases in 2014 to 54.3 cases per 100 000 in 2015). From 2012 to 2016, the incidence rate fluctuates between 50 and 65 cases per 100 000. Cancers of female genitalia, breast, and digestive system were the most common types in female and males, respectively.